2014
DOI: 10.1166/jnn.2014.8985
|View full text |Cite
|
Sign up to set email alerts
|

Mo-Doped TiO<SUB>2</SUB> with Enhanced Visible Light Photocatalytic Activity: A Combined Experimental and Theoretical Study

Abstract: In this paper, the effects of Mo doping on the geometrical, electronic, optical, and photocatalytic properties of TiO2 have been investigated theoretically and experimentally. The density functional theory based calculations show that Mo doping creates impurity states (Mo 4d) below the conduction band of TiO2 and the Fermi level is pinned inside the conduction band verifying n-type doping nature of the Mo in TiO2, which enhances its visible light absorption. Anatase TiO2 particles with Mo contents of 0.08, 0.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…For the stoichiometric system (figure 2(a)), Mo s-states emerge at the CBM of the TiO 2 host and the Mo d-states overlap with the titania CB. The emergence of Mo-derived defect states below the CBM was reported by the GGA studies of Mo-doped TiO 2 [36,63]. Mo dstates below the CBM were identified in these studies but there was no discussion of the Mo s-states.…”
Section: Dftmentioning
confidence: 96%
See 2 more Smart Citations
“…For the stoichiometric system (figure 2(a)), Mo s-states emerge at the CBM of the TiO 2 host and the Mo d-states overlap with the titania CB. The emergence of Mo-derived defect states below the CBM was reported by the GGA studies of Mo-doped TiO 2 [36,63]. Mo dstates below the CBM were identified in these studies but there was no discussion of the Mo s-states.…”
Section: Dftmentioning
confidence: 96%
“…The ionic radius of Mo 6+ is almost identical to that of Ti 4+ , being 0.062 nm and 0.068 nm, respectively, and, therefore, Mo 6+ ions could easily replace Ti 4+ ions in the anatase crystal lattice [34,35]. This kind of doping would minimise the lattice distortion [35,36]. Mo doping could also generate energy states within the band gap of TiO 2 to enhance the light absorption and minimise the electron-hole recombination [35][36][37].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Dieterle et al [38] indicated that the absorption bands from 0.55 to 3. [39,40]. This represented that the synthesis methods of precipitation and impregnation were both successful for doping Mo into the structure or depositing MoO x on the surface of TNTs.…”
Section: Materials Synthesis and Characterizationmentioning
confidence: 99%
“…But the photocatalytic reactivity of TiO 2 under visible light condition (wavelength greater than 387.5 nm) still remains low after the addition of ZrO 2 to TiO 2 . In order to utilize the visible part of the solar spectrum, or under general illumination conditions, two approaches could be undertaken with one being doping transition metals into TiO 2 [4,5], and the other being forming defects of TiO catalyst compounds [6,7]. Although doping transition metals can improve the reactivity of TiO 2 under visible light, the TiO 2 reactivity under ultraviolet light would decrease correspondingly.…”
Section: Introductionmentioning
confidence: 99%